ULTRAPOTASSIC CLINOPYROXENE FROM THE KUMDY-KOL MICRODIAMOND MINE, KOKCHETAV COMPLEX, KAZAKHSTAN: OCCURRENCE, COMPOSITION AND CRYSTAL-CHEMICAL CHARACTERIZATION - Bindi L.; Menchetti S.; Safonov O.G.; Yapaskurt V.O.; Perchuk L.L. (My University, 2003)
We report data on the composition and crystal structure of the most K-rich (3.61 wt% K2O) natural clinopyroxene yet discovered. The studied crystal was found as a tiny inclusion in garnet from a garnet-clinopyroxene rock of the Kumdy-Kol microdiamond mine. Kokchetav complex, Northern Kazakhstan. Microprobe analysis yields the formula (Ca0.61Fe0.13Mg0.04Mn0.01K0.17Na0.05) (Al0.61Mg0.39)(Si1.61Al0.39)O 6.00. Lattice parameters are: a = 9.773(1), b = 8.926(1), c = 5.269(1) Å, β = 105.75(1)°. The structure was refined up to Rall = 2.42% using 982 independent reflections. Substitution of K for Ca causes significant modification of the average structure. No evidence for an additional M2' position was found. Crystal-chemical characteristics are compared with published data on both natural and synthetic K-bearing clinopyroxenes.
Keywords: Clinopyroxene